Didactics of Historical-Cultural Heritage QR Codes and the TPACK Model: An Analytic Revision of Three Classroom Experiences in Spanish Higher Education Contexts - Delfín Ortega-Sánchez; Isabel María Gómez-Trigueros (Education Sciences, 2019)
This study aims to establish a first reference didactic and methodological framework for the operational and effective integration of Quick Response (QR) codes in the training of Social Sciences teachers in Primary Education, paying special attention to the integrated acquisition of social, civic, and digital competences in the framework TPACK (Technological Pedagogical Content Knowledge). With this purpose, it specifies the didactic potential of these new technological resources in the teaching-learning of the Social Sciences, its eventual integration in the design and implementation of teaching innovation projects for this educational stage, and its capacity for the acquisition of competence digital teaching in Primary Education teachers in initial training. In this sense, the work explores a selection of classroom experiences and research and innovation proposals, pioneers in the field of Social Sciences Didactics in Spain, with the aim of offering an approximation and status of the didactic treatment of History and, particularly, the historical-cultural heritage in the formation of Primary Education teachers.